2010
DOI: 10.1080/08870441003611577
|View full text |Cite
|
Sign up to set email alerts
|

Predicting depressive symptoms among the mothers of children with leukaemia: A caregiver stress model perspective

Abstract: The aim of this study was to find out the predictors of depressive symptoms of mothers of children with leukaemia. The potential predictors were chosen in the light of the caregiver stress model [Pearlin, Mullan, Semple, and Skaff, 1990. Caregiving and the stress process: An overview of concepts and their measures. The Gerontologist, 30(5), 583-594.], which examines the caregiver stress as composed of many factors such as the background variables, primary and secondary stressors, mediators and psychological he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 21 publications
4
31
0
6
Order By: Relevance
“…While counterintuitive, this finding is consistent with previous caregiving research (Aranda & Hayman-White, 2001; Demirtepe-Saygili & Bozo, 2011; Given et al, 2004). It has been posited that the type of task is of greater importance than the actual time spent for caregiving or the number of tasks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While counterintuitive, this finding is consistent with previous caregiving research (Aranda & Hayman-White, 2001; Demirtepe-Saygili & Bozo, 2011; Given et al, 2004). It has been posited that the type of task is of greater importance than the actual time spent for caregiving or the number of tasks.…”
Section: Discussionsupporting
confidence: 91%
“…An additional explanation is that caregiving tasks for children might be perceived differently than tasks in caring for an elderly family member. Caregiving for a child may not be perceived as an extra burden but rather part of their parenting role (Demirtepe-Saygili & Bozo, 2011). In addition, due to this perception that care is part of the parenting role, mothers in this study may have underestimated the amount of care delivered to their technology-dependent child.…”
Section: Discussionmentioning
confidence: 99%
“…from work) were associated with higher distress, anxiety, depression and PTSS in parents (Fotiadou et al . ; Demirtepe‐Saygili & Bozo ; Norberg et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…A study on caregivers of people with amyotrophic lateral sclerosis also indicated that depression and anxiety are effectively related to the burden experienced by carers (Pagnini et al, ). Finally, mothers of children with leukaemia complained severe depressive symptoms (Demirtepe‐Saygılı & Bozo, ).…”
Section: Introductionmentioning
confidence: 99%